Subaltern Ethics in Contemporary Scottish and Irish Literature Tracing Counter-Histories - Lehner, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book develops an innovative Irish-Scottish postcolonial approach by galvanizing Emmanuel Levinas' ethics with the socio-cultural category of the 'subaltern'. It sheds new light on contemporary Scottish and Irish fiction, exploring how these writings interact with the recent restructuring of the three state-formations in Ireland and Scotland.